2019
DOI: 10.17816/transsyst20195126-41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of public effectiveness of the strategy for development of speed urban transport

Abstract: М. В. Фѐдорова Петербургский государственный университет путей сообщения Императора Александра I (Санкт-Петербург, Россия) ОЦЕНКА ОБЩЕСТВЕННОЙ ЭФФЕКТИВНОСТИ СТРАТЕГИИ РАЗВИТИЯ СКОРОСТНОГО ГОРОДСКОГО ТРАНСПОРТА Аннотация: Оценка общественной эффективности стратегии скоростного городского транспорта является заключительным этапом формирования стратегии развития скоростного транспорта.Стратегия развития скоростного городского транспорта отличается следующими основными характеристиками: значительные первоначальны… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Fedorova (2019) indicated that feasibility and socio-economic studies of mega infrastructure projects such as rail and metro networks are crucial for sustainable planning of different construction activities of such projects. Many recent studies can be seen in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Fedorova (2019) indicated that feasibility and socio-economic studies of mega infrastructure projects such as rail and metro networks are crucial for sustainable planning of different construction activities of such projects. Many recent studies can be seen in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other research (Zhang et al, 2021;Boadu et al, 2020) identified the critical factors influencing the safety of Chinese subway construction projects that are directly related to construction projects feasibility. Fedorova (2019) indicated that feasibility and socio-economic studies of mega infrastructure projects such as rail and metro networks are crucial for sustainable planning of different construction activities of such projects. Many recent studies can be seen in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation